THE HISTORY OF GREAT BRITAIN. ENGLAND HISTORICAL CHART (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article delves into the intricate historical journey of Great Britain, focusing primarily on England's pivotal role in shaping the nation's identity. The narrative meticulously navigates through key epochs, offering a panoramic view of England's evolution from ancient times to the modern era. The annotation highlights the fusion of cultures, such as the amalgamation of Anglo-Saxon and Norse traditions, and the consequential changes that left enduring imprints on England's language, law, and societal norms. Notable rulers and dynasties, from the Tudors to the Stuarts, are examined, shedding light on their contributions and the broader impact on England's historical trajectory.